Confronting Antisemitism from the Perspectives of Christianity, Islam, and Judaism - Mayerhofer, Kerstin; Porat, Dina; Lange, Armin; Schiffman, Lawrence H. (De Gruyter, 2020)
This volume engages with antisemitic stereotypes as religious symbols that express and transmit a belief system of Jew-hatred. These religious symbols are stored in Christian, Muslim and even today$1 (Bs secular cultural and religious memories. This volume explores how antisemitic religious symbol systems can play a key role in the construction of group identities.s
English